MENGEJAR RAKSASA BARU EKONOMI EKPLORASI TERHADAP JALAN PEMBANGUNAN INDONESIA DAN BRIC - Chandra T. Putra (Fakultas Seni Rupa dan Desain ITB, 2009)
The term BRIC (Brazil, Russia, India, and China) which expresses 4 high-growing and large-economic-size emerging countries is introduced in a paper by Wilson and Purushothaman (both represent Goldman Sachs). The paper predicts that by 2050, those 4 countries will outshadow the present sum of major economies that we now know as G6. The prediction also notices that Indonesia will be placed as the 7th largest economies in 2050. With the present global economic downturn and how each country responds the situation, this prediction might eventually change. The negative growth of many developed countries and the resilience of some emerging economies may cause an even earlier proof of the prediction. Indonesia that's been predicted in the next line of the new giants also shows a strong resilience in the present financial crisis, side by side with China and India. Would it be the positive sign of the future development of Indonesia? This paper gives some perceptives that though Indonesia is lagged in economic performance behind the BRIC especially after the 1998 economic crisis, Indonesia shows a strong resilience in the effect of present global financial crisis. Indonesia can be part of the upcoming economic giants, but it needs to enhance its competitiveness. This paper also comprises the comparison of BRIC's and Indonesia's development path, and also the future potentials and resistance that Indonesia might meet during the path to be the next giants.